Teknik Pemijahan Ikan Nila Nirwana (Oreochromis niloticus) Pada Sistem Konvensional dan Sistem Happa di Ernawati Farm Galunggung Tasikmalaya - Wijaya, Megawati; Nurjanah, Lilis (Jurnal Akuakultur Sungai dan Danau, 2025)
The success of Nile tilapia (Oreochromis niloticus) cultivated is influenced by many factors, such as broodstock and fry quality, water quality, pond and feed management, and also the control of pests and diseases. The selection of appropriate spawning containers is critical, as it affects broodstock adaptation, comfort, behavior, and overall spawning success. This study aims to compare spawning performance of Nile tilapia in conventional earthen ponds and with hapa systems. A qualitative descriptive methodology was employed, with data collected at Ernawati Farm Galunggung (EFG), Tasikmalaya. Results demonstrated that larval productivity in the conventional earthen pond system was more stable than in the hapa system. Specifically, larval output over 10 spawning cycles with three replicates ranged from 30,000 to 94,000 individuals in the conventional system, compared to 10,000 to 110,000 individuals in the hapa system. The greater swimming space available in the conventional system likely facilitated nest building prior to spawning, contributing to increased productivity stability. In contrast, the restricted movement in the hapa system appeared to induce stress among broodstock, resulting in less consistent larval output. Larval survival rates were 100% in both systems, with larvae harvested at three days post-hatching.